Order or disorder? Impaired Hebb learning in dyslexia. - Arnaud Szmalec; Maaike Loncke; Mike Page; Wouter Duyck (2011)
The present study offers an integrative account which proposes that dyslexia and its various associated cognitive impairments reflect an underlying deficit in the long-term learning of serial-order information, here operationalized as Hebb repetition learning.In non-dyslexic individuals, improved immediate serial recall is typically observed when one particular sequence of items is repeated across an experimental session, a phenomenon known as the Hebb repetition effect.Starting from the critical observation that individuals with dyslexia seem to be selectively impaired in cognitive tasks that involve processing of serial order, the present study is the first to test and confirm the hypothesis that the Hebb repetition effect is affected in dyslexia, also in non-verbal modalities.We present a theoretical framework in which the Hebb repetition effect is assumed to be a laboratory analogue of naturalistic word learning, on the basis of which we argue that dyslexia is characterized by an impairment of serial-order learning that affects language learning and processing.